by mkania
Tags: 89uj
mkania is offline
Oct5-05, 08:03 PM
P: 1
Okay, here is my approach. Let me know if you think it makes sense.

We have c = f\lambda and [tex] c = \sqrt{(\gamma RT)/M} [/tex]. In the fundamendal mode, \lambda = 2L. So

2f_\mathrm{He}L = \sqrt{(\gamma_\mathrm{He}RT)/M_\mathrm{He}} (1)


2fL = \sqrt{(\gamma_\mathrm{air}RT)/M_\mathrm{air}} (2)

Dividing (1) by (2),

f_\mathrm{He}/f = \sqrt{(\gamma_\mathrm{He}M_\mathrm{air})/(\gamma_\mathrm{air}M_\mathrm{He})}


f_\mathrm{He} = f\sqrt{(\gamma_\mathrm{He}M_\mathrm{air})/(\gamma_\mathrm{air}M_\mathrm{He})}
Phys.Org News Partner Science news on Phys.org
Simplicity is key to co-operative robots
Chemical vapor deposition used to grow atomic layer materials on top of each other
Earliest ancestor of land herbivores discovered
mathmike is offline
Oct5-05, 08:34 PM
P: 212
your latex is f---ed up

Register to reply